PERINTISAN PUSAT KREATIVITAS MASYARAKAT (PKM) DI KAMPUNG NANGORAK KABUPATEN SUMEDANG DALAM MENYAMBUT PEMBERLAKUAN DESA WISATA - Trisna Gumilar; Trisna Prabosmoro; Rasus Budhiyono (IAIN Purwokerto, 2018)
Abstract: This village is located in Sumedang Agrotechnobusiness Area (KAS) and has promising natural potential and population potential. Besides being flanked by the tourist village of Kampung Toga, Gunung Puyuh, Tea Plantation, the community has traditions of art and other cultural activities. However, these potentials have not been integrated into an economic power and seem to walk independently. Such potential can continue to grow. To compensate for the socio-economic development, the community needs to prepare itself for the advancement of the times in order to keep loving the region, tradition and culture, and having a creative soul. Therefore, it was pioneered and initiated the establishment of a Community Learning Activity Center (PKBM) or creativity community center (PKM) as a place or means of information for learning and doing creation. Keywords: Creativity Community Center, Enforcement, and Village.